اختلاجات الوليد، الأنماط السريرية والسببيات. - غالية مازن; أصلان سمير; شحود وليد (Latakia University Journal -Medical Sciences Series, 2018)
Objective: The main objectives: - Study of the proportion and distribution of clinical patterns of seizures in neonates. - Identify the pathogens that cause them. Secondary objectives: - Study of the relationship between seizures and gestational age, birth weight, type of birth, and initiation time. Methods: Type of study: descriptive case series. The study included neonates with seizures (up to the age of 28 days for term infant and up to 44 weeks of gestational age for preterm infants) who were accepted in the children section of Tishreen University Hospital in Lattakia during the study period. Excluded from study: None. The clinical examination and the pathological story were considered a guide for subsequent laboratory and radiological investigations. Laboratory analyzes were conducted for all patients: CBC, Liver and Kidney Functions, CRP, Serum Sugar, Serum electrolytes. Additional surveys were conducted for some patients according to the orientation of the diagnosis: Brain ECO , CSF analysis , brain CT , serum Mg , blood ammonia , LDH , PT , PTT , CKP , EEG , ABG , TORCH Antibodies , Blood culture , Ophthalmoscopy. Results:The seizures were recorded at 42 births, constituting 6.14% of the total 683 newborns admitted to the neonatal and neonatal ward at Tishreen University Hospital during the study period. The number of males is 31, which constitutes 73.8% of the sample, and females 11, which constitutes 26.2% of the sample, with significant statistical significance (p v less than 0.05). The highest rate of seizures occurred in preterm infants (57.1% vs 42.9% at the time of pregnancy), with significant statistical significance (p v less than 0.05). The neonates with a weight between 1500-2500g was the largest proportion of the study sample, with significant statistical significance (p v less than 0.05). The most frequent pattern of seizures was the subtle 38.1%, followed by the clonic 26.2%, the tonic 21.4%, and the myoclonic14.3%, respectively, with significant statistical significance (p v less than 0.05). Causes of seizures: Ischemic encephalopathy 40.5%, infection 26.2%, intracranial hemorrhage 14.3%, Hypoglycaemia, Hypocalcemia, Hypomagnesemia 12%, intrauterine infection 2.4%, Kernicterus 2.4%, Brain Malformation 2.4%. Even though seizures are associated greater with Caesarean delivery 54.8%, we did not notice a statistically significant relationship between the delivery method and the occurrence of convulsion (p v greater than 0.05). The highest incidence of seizures occurred in the first 2 days of neonatal age (42.9%) With significant statistical significance (p v less than 0.05). هدف الدراسة: الأهداف الرئيسية: - دراسة نسبة وتوزع الأنماط السريرية للاختلاج عند الولدان. - تحديد الإمراضيات المسببة لها. الأهداف الثانوية: -دراسة العلاقة بين الاختلاج وكل من العمر الحملي، ووزن الولادة، ونوع الولادة، وزمن بدء الاختلاج. طريقة البحث والمرضى: نوع الدراسة: وصفية (DESCRIPTIVE CASE SERIES). المشمولون بالدراسة: شملت الدراسة الولدان المصابين باختلاج (حتى عمر 28 يوم لتامي الحمل وحتى 44 أسبوع حملي مصحح بالنسبة للخدج)، المقبولين في قسم الأطفال مشفى تشرين الجامعي باللاذقية خلال مدة الدراسة. المستبعدون من الدراسة: لا يوجد. اعتبر الفحص السريري والقصة المرضية مرشداً للاستقصاءات المخبرية والشعاعية اللاحقة. تم إجراء تحاليل مخبرية لجميع مرضى الدراسة: تعداد عام وصيغة، شوارد المصل، وظائف الكبد والكلية، CRP، سكر المصل وتم اجراء استقصاءات إضافية لبعض مرضى الدراسة وفق التوجه للتشخيص: ايكو دماغ عبراليافوخ، بزل CSF (تعداد وصيغة وزرع)، طبقي محوري للدماغ، مغنيزيوم المصل، أمونيا ولاكتات الدم، CPK، PT، PTT، تخطيط دماغ كهربائي، غازات دم شرياني، زرع دم، أضداد torch، تنظير قعر العين. النتائج: سجلت الاختلاجات عند 42 وليد وهو ما يشكل 6.14% من مجموع حديثي الولادة البالغ 683 المقبولين في شعبة الحواضن وحديثي الولادة في مشفى تشرين الجامعي خلال مدة الدراسة. بلغ عدد الذكور 31 وهو يشكل 73.8% من العينة، وال إناث11 وهو يشكل 26.2% من العينة، مع دلالة إحصائية هامة (p v أقل من 0.05). حدثت النسبة الأكبر من الاختلاجات عند ال خدج57.1 %، مقابل 42.9% عند تامي الحمل، مع دلالة إحصائية هامة (p v أقل من 0.05). شكل الولدان ذوي الوزن بين 1500-2500غ النسبة الأكبر من عينة الدراسة، مع دلالة إحصائية هامة (p v أقل من 0.05). أكثر الأنماط الاختلاجية تكراراً هو النمط الدقيق38.1 % يليه الرمعي 26.2% ثم المقوي 21.4% ثم الرمعي العضلي 14.3%، مع دلالة إحصائية هامة (p v اقل 0.05). أسباب الاختلاج: اعتلال الدماغ الإقفاري 40.5%، ثم الانتان 26.2%، ثم النزف داخل القحف 14.3%، نقص سكر، كلس، مغنيزيوم 12%، انتان ضمن الرحم 2.4%، يرقان نووي 2.4%، تشوه دماغي 2.4%. رغم ترافق الإختلاج مع الولادة القيصرية بشكل أكبر54.8% إلا أننا لم نلاحظ وجود علاقة هامة احصائيا بين طريقة الولادة وحدوث الاختلاج (p v أكبر من 0.05). حدث الإختلاج بنسبة أعلى في أول يومين من عمر الولدان 42.9%. مع دلالة إحصائية هامة (p v أقل من 0,05).